2014
DOI: 10.15252/embj.201488896
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded protein response‐induced ER dj3 secretion links ER stress to extracellular proteostasis

Abstract: The Unfolded Protein Response (UPR) indirectly regulates extracellular proteostasis through transcriptional remodeling of endoplasmic reticulum (ER) proteostasis pathways. This remodeling attenuates secretion of misfolded, aggregation-prone proteins during ER stress. Through these activities, the UPR has a critical role in preventing the extracellular protein aggregation associated with numerous human diseases. Here, we demonstrate that UPR activation also directly influences extracellular proteostasis through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
121
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(125 citation statements)
references
References 99 publications
(148 reference statements)
3
121
0
1
Order By: Relevance
“…Extracellular protein aggregation can also be attenuated by activating the unfolded protein response (UPR), which functions to regulate proteostasis (quality control) in the endoplasmic reticulum (ER) and in downstream compartments of the secretory pathway 157, 158 , including in the extracellular space 178 . The UPR signaling pathway comprises three arms activated downstream of the ER transmembrane stress-sensor proteins, IRE1, ATF6, and PERK.…”
Section: Strategies To Target the Process Of Protein Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular protein aggregation can also be attenuated by activating the unfolded protein response (UPR), which functions to regulate proteostasis (quality control) in the endoplasmic reticulum (ER) and in downstream compartments of the secretory pathway 157, 158 , including in the extracellular space 178 . The UPR signaling pathway comprises three arms activated downstream of the ER transmembrane stress-sensor proteins, IRE1, ATF6, and PERK.…”
Section: Strategies To Target the Process Of Protein Aggregationmentioning
confidence: 99%
“…Both the selective degradation of an energetically compromised TTR variant and the global reduction in extracellular concentrations of destabilized TTR will reduce the TTR aggregation propensity in the extracellular space. Moreover, ATF6 activation results in the secretion of an Hsp40 chaperone, ERdj3, which further reduces aggregation of amyloidogenic proteins in the extracellular space 178 . Stress-independent activation of UPR-associated transcription factors has also recently been shown to reduce the secretion of a destabilized amyloidogenic LC without affecting the secretion of an energetically normal LC 148 .…”
Section: Strategies To Target the Process Of Protein Aggregationmentioning
confidence: 99%
“…Moreover, consistent with previous findings showing increased plasma TTR levels after tafamidis treatment [5, 7], total TTR levels measured by quantitative Western blotting also increased in the tafamidis-treated samples (Figure S2). This is due to a pharmacologic chaperoning effect–tafamidis enters the endoplasmic reticulum of liver cells, binds to the WT TTR tetramer in the endoplasmic reticulum and shifts the linked folding and assembly process toward tetramer formation, thus enabling more WT TTR tetramer to be formed and secreted [31, 32]. …”
Section: Resultsmentioning
confidence: 99%
“…Recently, interesting information on the importance of extracellular chaperones for maintaining the proteostasis landscape has appeared [49] and these concepts might be transferrable to extracellular PDIs like AGR2. Genereux et al [49] demonstrated that UPR activation induces secretion of the ER chaperone ERdj3.…”
Section: Agr2 As An Endoplasmic Reticulum Protein Disulphide Isomerasementioning
confidence: 99%
“…Genereux et al [49] demonstrated that UPR activation induces secretion of the ER chaperone ERdj3. Secreted ERdj3 binds misfolded proteins in the extracellular space, attenuates protein aggregation, and reduces proteotoxicity of the disease-associated toxic prion protein.…”
Section: Agr2 As An Endoplasmic Reticulum Protein Disulphide Isomerasementioning
confidence: 99%